PENGIMBASAN PRAKTIK BAIK TENTANG IMPLEMENTASI KURIKULUM MERDEKA - Dewi, Citra; Bendriyanti, Rita Prima; Selviani, Diah; Lestari, Monica Indah (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Implementation is the implementation of a plan that has been prepared or assembled in a thorough and detailed manner. In implementing the independent curriculum, especially at SDN 17 Benteng, there are stages of planning, implementation and evaluation. Where, at the planning stage as a school principal you have to plan by making a coaching schedule for all teachers regarding important materials in the independent curriculum. At the implementation stage, the selected teachers create a learning plan that will be given to their students which consists of a new learning paradigm that focuses on active student learning, strengthening Learning Achievements (CP), and understanding learning material through differentiated teaching modules that are appropriate to student learning material. , as well as understanding in strengthening the Pancasila Student Profile Strengthening Project (P5). And at the evaluation stage, the teacher is able to prepare and formulate lessons that will be carried out the next day in each lesson chapter in strengthening the material in each lesson chapter. The Project for Strengthening the Profile of Pancasila Students must first be evaluated by the teacher in order to adjust the needs and characteristics of each student.